2011
DOI: 10.1177/0300985811409251
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Coxiella-like Infection With Myocarditis and Hepatitis in an Eclectus Parrot (Eclectus roratus)

Abstract: A multiorgan infection with a Coxiella-like organism was determined to be the cause of death of a female eclectus parrot(Eclectus roratus). The diagnosis was based on gross lesions, histopathology, Gimenez and Gram special stains, immunohistochemistry, electron microscopy, and polymerase chain reaction amplification and sequencing of a bacterial 16s rRNA gene fragment isolated from hepatic and cardiac tissue. Gross postmortem examination revealed multifocal to coalescing foci of hepatic necrosis. The most sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 10 publications
1
22
0
Order By: Relevance
“…There are yet to be any reports of human or animal infections with Coxiella- like bacteria from ticks. However, avian infections of Coxiella -like bacteria have been reported even though there is no established link to ticks (Shivaprasad et al 2008, Vapniarsky et al 2012). Therefore, the potential of these Coxiella -like bacteria causing zoonotic infections merits further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…There are yet to be any reports of human or animal infections with Coxiella- like bacteria from ticks. However, avian infections of Coxiella -like bacteria have been reported even though there is no established link to ticks (Shivaprasad et al 2008, Vapniarsky et al 2012). Therefore, the potential of these Coxiella -like bacteria causing zoonotic infections merits further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, host-microbe relationships should be best described as a broad continuum, as intermediate states and transitions between states occur frequently. Several maternally-inherited tick symbionts are remarkable examples of this continuum, as recent literature has reported that certain symbionts may be transmitted to vertebrates following tick bite, as will be detailed further in this section (Shivaprasad et al, 2008; Woc-Colburn et al, 2008; Vapniarsky et al, 2012; Bazzocchi et al, 2013; Edouard et al, 2013; Angelakis et al, 2016; Seo et al, 2016a; Bonnet et al, 2017). Most importantly, some of these symbionts have the potential to opportunistically infect vertebrate hosts, including humans.…”
Section: Tick Symbionts Can Be Opportunistic Vertebrate Pathogensmentioning
confidence: 99%
“…Birds are commonly infected with C. burnetii without apparent clinical signs, but in contrast show pathology when infected with Candidatus Coxiella avium, a pleomorphic Coxiella-like organism multiplying in macrophage vacuoles and leading to inflammation of liver, lung and spleen or systemic infection and death of the host (Shivaprasad et al 2008, Vapniarsky et al 2012. Further diversity amongst the genus has been described with reports of Coxiellalike organisms as endosymbionts among several species of ticks , with extremely high (close to 100%) infection frequency.…”
Section: Coxiella-like Organismsmentioning
confidence: 99%